Kayla Moore: capstone - Moore, Kayla, artist (Colorado State University. Libraries, 2015)
The artist's statement: Dealing with the themes of reaction and emotional response, both first and second hand, communicated through a balance of intentional mark making and mediated accident, I explore what it means to be an individual amongst many. My individual perspective and experience serves as a catalyst through which I can then strive to communicate with others on an intimate level, unique to each viewer. There exists a tie between us as human beings, an empathetic umbilical cord. Along with this primal connection, exists a barrier separating us that only allows us to experience the life of another through our own perspective. I wish to delve into the depths of this deep unnamed connection, and to explore brief moments of understanding as well as empathetic response, while personally trudging through my own nostalgia and memories. Beginning in a place of personal reflection, exploration of mental illness, and anxious tendencies, my work engages with subtle yet raw formal language that serves as the avenue through which honest, yet guarded dialogue can begin. In my most current body of work, I strive to inflict emotional response, whether it is apathy, empathy, or sympathy. Using my own personal themes of perceived gender roles, mental health, coping, and a search for home; the work in this show is my vessel through which I can function as a mirror where my viewer's own unique existence can be acknowledged and validated. This work is my way of saying that because I have felt and struggled with these things, I believe the things you have gone through matter, what you have to say matters. It is my way of saying, "I see you, and you're going to be just fine."
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing